2015
DOI: 10.1097/bpo.0000000000000308
|View full text |Cite
|
Sign up to set email alerts
|

Internal Fixation of Unstable In Situ Osteochondritis Dissecans Lesions of the Capitellum

Abstract: Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…We identified 6 studies 6 , 7 , 12 , 23 , 28 , 31 that evaluated return-to-sport data after fixation of capitellar OCD lesions. Several methods of fixation were used, including hydroxyapatite pins, K-wires, and Herbert screws.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified 6 studies 6 , 7 , 12 , 23 , 28 , 31 that evaluated return-to-sport data after fixation of capitellar OCD lesions. Several methods of fixation were used, including hydroxyapatite pins, K-wires, and Herbert screws.…”
Section: Resultsmentioning
confidence: 99%
“…Only 8 studies 7 , 8 , 16 , 23 , 25 , 26 , 30 , 31 reported a diameter for size of the OCD lesion undergoing treatment. Sizes of lesions were similar between the debridement group (13.35 mm), the fixation group (11.93 mm), and the OAT group (13.87 mm).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When using the outside in technique, fluoroscopy Discontinuity and non-circularity of the chondral surface signal of the capitellum and no high signal interface apparent between the lesion and the floor Itsubo et al [25] is used to identify the lesion and an ACL guide can be useful for targeting the lesion. When the OCD lesion is intact but unstable, internal fixation has been found to be successful for larger osteochondral fragments [45]. After identification of the lesion arthroscopically, the fragment is gently elevated and the bed is prepared by removing sclerotic bone and fibrous tissue which can be enhanced with cancellous bone graft.…”
Section: Arthroscopic Managementmentioning
confidence: 99%